"The Standard Procedure" for Investigation of Oral Neutrophils in Oral Diseases - Peter Østrup Jensen; Pernille Dukanovic Rikvold; Kristine Røn Larsen; Mette Rose Jørgensen; Camilla Kragelund (Hindawi Limited, 2023)
Aim. There is need of an objective "standard procedure" that is reliable and clinically applicable for estimating oral neutrophil content in relation to oral diseases. Methods. Forty-one patients with suspected oral candidosis (OC) and nine healthy controls with no oral mucosal disease were flushing with 10 ml mouth rinse (MR) (sterile phosphate-buffered saline) for 1 min. Aliquots were stored on different conditions to explore stability, storage, and fixation conditions for analysis by flow cytometry. Results. The optimal storage and fixation condition for MR was by fixation 1 : 1 in 10% formalin and stored at 5°C. This procedure yielded stable results up to 7 days after collection. The ability of the optimized method to relate oral neutrophils to inflammation was demonstrated by the significantly higher number of neutrophils in patients with primary OC (p=0.0334) compared to healthy controls. Conclusion. This method is rapid, reliable, and clinically applicable for establishing the content of oral neutrophils. We demonstrate increased density of oral neutrophils in the MR of patients with OC. The potential of the method is to be "the standard procedure" for investigation of the oral inflammation in patients with oral diseases as it is noninvasive and provides high stability, clinical relevance, and minimal handling.